High-Level Heat Resistance of Spores of Bacillus amyloliquefaciens and Bacillus licheniformis Results from the Presence of a spoVA Operon in a Tn1546 Transposon - Berendsen, Erwin M.; Koning, Rosella A.; Boekhorst, Jos; de Jong, Anne; Kuipers, Oscar P.; Wells-Bennik, Marjon H. J. (Frontiers in Microbiology, 2016)
Bacterial endospore formers can produce spores that are resistant to many food processing conditions, including heat. Some spores may survive heating processes aimed at production of commercially sterile foods. Recently, it was shown that a spoVA operon, designated spoVA2mob, present on a Tn1546 transposon in Bacillus subtilis, leads to profoundly increased wet heat resistance of B. subtilis spores. Such Tn1546 transposon elements including the spoVA2mob operon were also found in several strains of Bacillus amyloliquefaciens and Bacillus licheniformis, and these strains were shown to produce spores with significantly higher resistances to wet heat than their counterparts lacking this transposon. In this study, the locations and compositions of Tn1546 transposons encompassing the spoVA2mob operons in B. amyloliquefaciens and B. licheniformis were analyzed. Introduction of these spoVA2mob operons into B. subtilis 168 (producing spores that are not highly heat resistant) rendered mutant 168 strains that produced high-level heat resistant spores, demonstrating that these elements in B. amyloliquefaciens and B. licheniformis are responsible for high level heat resistance of spores. Assessment of growth of the nine strains of each species between 5.2°C and 57.7°C showed some differences between strains, especially at lower temperatures, but all strains were able to grow at 57.7°C. Strains of B. amyloliquefaciens and B. licheniformis that contain the Tn1546 elements (and produce high-level heat resistant spores) grew at temperatures similar to those of their Tn1546-negative counterparts that produce low-level heat resistant spores. The findings presented in this study allow for detection of B. amyloliquefaciens and B. licheniformis strains that produce highly heat resistant spores in the food chain.